Sub-millimetre observations of hyperluminous infrared galaxies - Farrah, D; Serjeant, S; Efstathiou, A; Rowan-Robinson, M; Verma, A (2002)
We present sub-mm photometry for 11 Hyperluminous Infrared Galaxies (HLIRGs) and use radiative transfer models for starbursts and AGN to investigate the IR emission. In all sources both a starburst and AGN are required to explain the IR emission. The mean starburst fraction is 35%, with a range spanning 80% starburst dominated to 80% AGN dominated. In all cases the starburst dominates at rest-frame wavelengths >50 microns, with star formation rates >500 solar masses per year. The trend of increasing AGN fraction with increasing IR luminosity seen in IRAS galaxies peaks in HLIRGs, and is not higher than the fraction seen in bright ULIRGs. The AGN and starburst luminosities correlate, suggesting that a common physical factor, plausibly the dust masses, governs their luminosities. Our results suggest that the HLIRG population is comprised both of ULIRG-like galaxy mergers, and of young galaxies going through their maximal star formation periods whilst harbouring an AGN. The coeval AGN and starburst activity in our sources implies that starburst and AGN activity, and the peak starburst and AGN luminosities, can be coeval in active galaxies generally. When extrapolated to high-z our sources have comparable sub-mm fluxes to sub-mm survey sources. At least some sub-mm survey sources are therefore likely to be comprised of similar galaxy populations to those found in the HLIRG population. It is also plausible from these results that high-z sub-mm sources harbour heavily obscured AGN. The differences in X-ray and sub-mm properties between HLIRGs at z~1 and sub-mm sources at z~3 implies evolution between the two epochs. Either the mean AGN obscuration level is greater at z~3 than at z~1, or the fraction of IR-luminous sources at z~3 that contain AGN is smaller than that at z~1.